An evaluation of Indonesia's open proportional electoral system and its impact on party fragmentation in the 2024 general election : Evaluasi sistem pemilu proporsional terbuka di Indonesia dan dampaknya terhadap fragmentasi partai di Pemilu 2024 - Argoebie, Bella; Cindy; Muhammad Raffata Umar; Lia Wulandari (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2025)
This study looks at how the open-list proportional voting system in Indonesia affects political division and democratic representation in the 2024 elections. The research will find out if this system increases diversity in party beliefs or just creates more parties without really improving representation. Using a qualitative case study method, the research reviews secondary data from election results, party beliefs, and existing research to evaluate how the system affects political stability and leadership. The findings show that while the open-list system has improved political involvement by allowing voters to choose candidates directly, it has not significantly increased ideological representation.Mst parties are focused on a nationalist-Islamic direction, with some exceptions like the the Labor Party and PSI. Even though many parties are emerging, the division is mostly surface-level because major parties, like the Koalisis Indonesia Maju Plus, tend to centralize power instead of creating healthy competition. The system also worsens problems like high campaign cost, poor candidate management by parties, and money-driven politics, reducing its democratic value. The study concludes that the open-list system increases voter independence but needs changes to address its weaknesses. Suggested improvements include adopting a mixed voting system, developing party members better, improving voter education, and implementing stricter rules on campaign financing. These actions would help balance democratic representation with political stability and match the system with Indonesia’s constitutional principle of popular sovereignty.The research contributes to discussions on electoral reform and offers policy suggestions to strengthen Indonesia's democratic governance.